Foundations of a Relativity Marketing Theory - Kortam, Wael; Abbas, Abdelhameed (Archives of Business Research, 2021)
This research aims to open the way to review of the philosophical postulates and ideological pathways that govern the contributions in marketing theory, to reflect the scientific marketing truth. We do not mean by this to trace the history of marketing thought, but rather, a re-investigation of the logic of its existence and being. It is an attempt to re-explore and depart from the axioms that ruled marketing thought. Marketing theory emerged from being a scientific theory that can be true or false, to be an "ideology” defended by its supporters. From this point; this research set the foundation for developing a new general marketing theory based on the relativity concept, has the ability and adaptation to exceed the boundaries of “product, technology, time, place, context and customer”, acquires its being and existence from the verification of the current philosophy of marketing science, and considering the marketing experience